Manifestasi keterkaitan antara kekurangan personel dan beban kerja - Lestari, Lela; Rahayu, Markhamah; Yasmin, Annisa (Implementasi Manajemen & Kewirausahaan, 2022)
This study aims to determine employees' workload when there is a lack of personnel in the Learning & Development Department at PT Sumber Alfaria Trijaya Tbk Rembang Branch. This research is a descriptive study with a qualitative approach with data collection techniques in the form of observation, interviews, and documentation. Three informants in this study are employees in the position of training officer and recruitment officer. The results of this study indicate that the cause of the lack of personnel is the difficulty in finding human resources that match the company's qualifications. The shortage of personnel in the department then increased the workload of employees, so employees often came home late or continued work when they were at home. Efforts are being made to overcome the increasing workload by making a schedule/planning one month in advance and making a list of jobs as well as much coordination with time to request assistance for work that must be completed immediately according to the specified deadline.